AI-Based Human Resource Management Information System Design To Improve Organization Agility Presenting Society 5.0 - M. Refky Ramadan; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to design an Artificial Intelligence (AI)-based Human Resource Management Information System (HRMIS) to enhance organizational agility in supporting the implementation of Society 5.0. The study employed a library research method with a descriptive qualitative approach by analyzing relevant books, scientific journals, and academic publications related to human resource management, management information systems, artificial intelligence, and Society 5.0. The findings indicate that integrating AI into an HRMIS can optimize recruitment processes, employee data management, performance evaluation, competency mapping, training recommendations, and real-time decision support. Furthermore, the proposed system enhances the efficiency and effectiveness of human resource management while enabling organizations to respond more quickly and adaptively to dynamic environmental changes. Consequently, an AI-based HRMIS serves as a strategic solution for fostering organizational agility and supporting the realization of a human-centered, innovative, and sustainable Society 5.0.